Nitrogen-doped graphene quantum dots (N-GQDs) perturb redox-sensitive system via the selective inhibition of antioxidant enzyme activities in zebrafish. (June 2019) - Deng, Shun; Fu, Ailing; Junaid, Muhammad; Wang, Yan; Yin, Qian; Fu, Chen; Liu, Li; Su, Dong-Sheng; Bian, Wan-Ping; Pei, De-Sheng
Abstract: Graphene quantum dots (GQDs) are well-known for its potential applications for bioimaging, biosensor, and drug carrier in biomedicine. GQDs are well characteristic of intrinsic peroxidase-like catalytic activity, which is proven effective in scavenging the free radicals, such assuperoxide anion, hydrogen peroxide, and hydroxyl radical. GQDs are also well praised for its low in vivo and in vitro toxicity. Here, we found that nitrogen-doped GQDs (N-GQDs) can strongly disturb redox-sensitive system via the selective inhibition of endogenous antioxidant enzyme activities in zebrafish. The enzyme activities or transcription levels of a battery of hemoproteins including catalase (CAT), superoxide dismutase (SOD), respiratory chain complex I, complex Ⅲ, hemoglobin (Hb), and myeloperoxidase (MPO), were significantly suppressed by N-GQDs. We also found that N-GQDs activated the cytochrome P450 monooxygenase ( e.g. cyp1a ) and the associated aryl-hydrocarbon receptor repressors ( ahrr1 and ahrr2 ) in zebrafish embryos. Compared to the ultrasmall graphene oxide (USGO), N-GQDs exhibited stronger fluorescent permeability and tissue-specific bio-accumulative effects. Taken together, our findings highlighted that exposure to N-GQDs can disrupt endogenous antioxidant enzyme activities, possibly via the competitive inhibition of electron transfer process. Our results in this study provided solid data for biosafety evaluations of various types of GQDs, and created an alert for the future biomedical applications of N-GQDs.